2009
DOI: 10.1007/s10803-009-0704-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Vineland Adaptive Behavior Scales in Young Children with Autism Spectrum Disorders at Different Cognitive Levels

Abstract: Vineland Adaptive Behavior Scales (VABS) data were examined in a large sample of young children with ASD (n = 290) of varying cognitive levels. IQ was higher than VABS composite score among high functioning children only; the opposite pattern was found in lower IQ subgroups. Profile analysis of VABS domains across cognitive levels demonstrated different profiles in different subgroups. A characteristic "autism profile" was found for most subgroups for Age Equivalents but not Standard Scores. In a small set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
196
8
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(252 citation statements)
references
References 33 publications
37
196
8
6
Order By: Relevance
“…Including adaptive behaviour testing in the diagnosis, as achieved systematically only in Iceland, may decrease the number of falsely positive cases (thus wrongly considered with severe intellectual disability). 20,21 In spite of this, the highest prevalence was found in Iceland. This may be explained by the fact that the adaptive behaviour scores appear to be more important for those with higher intellectual scores, that is for those with mild intellectual disability, than for those with severe intellectual disability.…”
Section: Discussionmentioning
confidence: 97%
“…Including adaptive behaviour testing in the diagnosis, as achieved systematically only in Iceland, may decrease the number of falsely positive cases (thus wrongly considered with severe intellectual disability). 20,21 In spite of this, the highest prevalence was found in Iceland. This may be explained by the fact that the adaptive behaviour scores appear to be more important for those with higher intellectual scores, that is for those with mild intellectual disability, than for those with severe intellectual disability.…”
Section: Discussionmentioning
confidence: 97%
“…In ABA approach, firstly the baseline levels of target behaviors in individuals with ASDs should be operationally defined and measured; assessment instruments such as Vineland Adaptive Behavior Scale, AAIDD Adaptive Behavior Scale-School: Second Edition (ABS-S: 2) and Developmental Behavior Checklist (DBC) can be used to evaluate children abilities in different domains. Then, ABA intervention method is performed to alter target behaviors and finally, the rate of changing behavior can be revealed in the repeated measurement (81)(82)(83)(84)(85) In Iran, home based lovaas approach was performed for treating autism, and the results showed that it was effective to improve social interaction, speech and language, play and behavior skills in autistic children (86). Furthermore, the effect of Applied Behavior Analysis (ABA) intervention method was demonstrated on autistic children who had acquired significant improvements in suitable behaviors (87).…”
Section: Ghanizadeh (2011) Hypothesized That Glycine Site On the N-mementioning
confidence: 99%
“…Adaptive functioning in children with ASD as measured on the Vineland Adaptive Behavior Scales is lower than predicted by IQ. 4,5 This gap between IQ and adaptive functioning tends to be wider in children with ASD and average IQ compared to those with intellectual disability. 6 Over time, many children with ASD do not keep pace with age mates on the Vineland, and standard scores may actually decline.…”
Section: Introductionmentioning
confidence: 99%